Nine lives to die : a Mrs. Murphy mystery - Brown, Rita Mae (Brown, Rita Mae. Mrs. Murphy mystery., 2014)
A busy holiday season for Harry, her husband, and her posse of pet detectives is interrupted by dark secrets from the community's past involving a cold case and a twenty-five-year-old love triangle.